Penerapan Belajar Kelompok Pada Pelajaran IPA Terpadu Untuk Meningkatkan Hasil Belajar Siswa SMP - Tirawati Bakara; Rusmauli Hutahayan (Jurnal Dedikasi Pendidikan, 2021)
This study aims to improve science learning outcomes in class VIII-2 SMP Negeri 2 Sunggal through group work methods. The method used is descriptive method with classroom action research design (classroom action research). Classroom action research was carried out in two cycles. This research was conducted at SMP Negeri 2 Sunggal. The subjects of this study were students of class VIII-2 SMP Negeri2 Sunggal, totaling 31 people. Based on the data analysis of the research results, the activeness of students in participating in learning increased from the first cycle of 71% in the sufficient category to 94% in the second cycle in the very good category. Student learning outcomes have increased with the average student learning outcomes in the first cycle, namely 75.48% in the sufficient category to 80.19% in the second cycle in the good category. Based on the results of the study, it was concluded that the group work method could improve science learning outcomes on the respiratory system material for class VII-2 SMP Negeri Sunggal.